2021
DOI: 10.3390/catal11040523
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Guaiacol Hydrodeoxygenation on Cu (111): Insights from Density Functional Theory Studies

Destiny Konadu,
Caroline Rosemyya Kwawu,
Richard Tia
et al.

Abstract: Understanding the mechanism of the catalytic upgrade of bio-oils via the process of hydrodeoxygenation (HDO) is desirable to produce targeted oxygen-deficient bio-fuels. We have used calculations based on the density functional theory to investigate the reaction mechanism of HDO of guaiacol over Cu (111) surface in the presence of H2, leading to the formation of catechol and anisole. Our analysis of the thermodynamics and kinetics involved in the reaction process shows that catechol is produced via direct deme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…Our earlier work 30 has shown that catechol is produced from guaiacol via direct demethylation into catecholate, followed by the concerted re-hydrogenation of catecholate into catechol. Anisole formation via the direct dehydroxylation of guaiacol followed by hydrogenation was found to be less favoured on Cu (111), both kinetically and thermodynamically.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our earlier work 30 has shown that catechol is produced from guaiacol via direct demethylation into catecholate, followed by the concerted re-hydrogenation of catecholate into catechol. Anisole formation via the direct dehydroxylation of guaiacol followed by hydrogenation was found to be less favoured on Cu (111), both kinetically and thermodynamically.…”
Section: Resultsmentioning
confidence: 99%
“…We observed that the C aryl -OH cleavage into anisole is more challenging than the C akyl -O bond cleavage into catechol, hence leading to the preferred formation of catechol over anisole. 30 To better understand, and thus be able to control, the catalytic deoxygenation reaction of phenolics on Cu (111) into pure hydrocarbon end-products, e.g. benzene, we have studied the detailed surface reaction mechanisms involved in the upgrade of the oxygenated phenolic compounds formed from guaiacol.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In comparison with metal catalysts like Cu and Pt, Mo 2 C has shown better deoxygenation ability. Recently, Konadu et al have reported a high electronic energy barrier of 200 kJ/mol for the dehydroxylation step from guaiacol, whereas it is more feasible on Mo 2 C with a low barrier of 78 kJ/mol (provided in Table S1). On the Pt(111) surface as well, high barriers of 240 and 244 kJ/mol for dehydroxylation and demethoxylation reaction steps, respectively, were observed .…”
Section: Resultsmentioning
confidence: 99%